Proceedings of the Fifth Euro-China Conference on Intelligent Data Analysis and Applications - Krömer, Pavel; Zhang, Hong; Liang, Yongquan; Pan, Jeng-Shyang (Advances in Intelligent Systems and Computing, 2019)
XVIII, 854 p. 437 illus., 289 illus. in color.